2022
DOI: 10.1038/s41391-022-00524-7
|View full text |Cite
|
Sign up to set email alerts
|

A phase 2 trial of avelumab in men with aggressive-variant or neuroendocrine prostate cancer

Abstract: Background Men with progressive neuroendocrine or aggressive-variant metastatic prostate cancer (NEPC/AVPC) have a poor prognosis and limited treatment options, and immunotherapy has not been tested in such patients. Methods We conducted an open label single center phase 2 trial (NCT03179410) of men with progressive NEPC/AVPC either defined by histology or AVPC criteria. Avelumab (10 mg/kg every 2 weeks) was administered until progression or unacceptable toxicity. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Some studies suggest that in patients undergoing ADT, neuroendocrine differentiation represents a possible escape mechanism leading to metastatic disease. More specifically these studies have demonstrated that preoperative CgA levels are associated with the response to docetaxel, enzalutamide, and abiraterone treatment 23–26 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies suggest that in patients undergoing ADT, neuroendocrine differentiation represents a possible escape mechanism leading to metastatic disease. More specifically these studies have demonstrated that preoperative CgA levels are associated with the response to docetaxel, enzalutamide, and abiraterone treatment 23–26 …”
Section: Discussionmentioning
confidence: 99%
“…More specifically these studies have demonstrated that preoperative CgA levels are associated with the response to docetaxel, enzalutamide, and abiraterone treatment. [23][24][25][26] In patients with CRPC some authors have evaluated genetic alterations, particularly in RB1, PTEN, and p53. 27,28 29 Moreover, the authors highlight the role of AR-low CGA-expressing cells that could predict resistance to neoadjuvant hormonal therapies.…”
Section: Discussionmentioning
confidence: 99%
“…While most patients respond, relapse is universal with a median survival of 1-2 years from the time of diagnosis ( 128 , 130 ). Though a trial of the single agent anti-PD1 inhibitor avelumab showed limited efficacy in men with NEPC (NCT03179410) ( 133 ) we await the results of trials incorporating checkpoint inhibitors with standard platinum doublets — as is now standard of care in small cell lung cancer.…”
Section: Clinical Trials In Nepcmentioning
confidence: 99%
“…Median radiographic PFS was 1.8 months and median OS was 7.4 months. The only patient with a complete response had NEPC with a central nervous system (CNS) metastasis and was found to have high microsatellite instability (MSI-H) disease due to a somatic MSH2 alteration [16 ▪ ]. Given this limited single-agent activity, combination immunotherapy is now being tested.…”
Section: Advanced Treatment: Progress and Uncertaintymentioning
confidence: 99%